FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA - Khoirun Ni’mah; Siti Rahayu Nadhiroh (Media Gizi Indonesia, 2015)
Stunting reflects chronic undernutrition during the most critical periods of growth and development in early life. Stunting can be caused by many factors such as child characteristic and socioeconomic factors. The aim of this study was to determine factors associated to stunting among children under five. This research was an analitycal observational study using case control design in Puskesmas Tanah Kali Kedinding, Surabaya. The samples were 34 subject for each group which were selected by simple random sampling technique. Data were analyzed by Chi Square and Fisher Exact test. The result showed that low birth length (OR=4,091; CI=1,162-14,397), children who did not get exclusive breastfeeding (OR=4,643; CI=1,328-16,233), low family income (OR=3,250; CI=1,150-9,187), low mother’s education (OR=3,378; CI=1,246-9,157), and lack of mother’s nutrition knowledge (OR=3,877; CI=1,410- 10,658) had significant relationship with stunting among children under five. There was a relationship between birth length, exclusive breastfeeding, family income, mother’s education and mother’s nutrition knowledge with stunting among children under five. The need for an integrated and multisectoral programs to increase family income, maternal education, maternal nutrition knowledge, and exclusive breastfeeding for reducing the incidence of stunting.Keywords: children, socioeconomic, stunting